BIO-MATRICONDITIONING BENIH DENGAN RIZOBAKTERI UNTUK MENINGKATKAN MUTU FISIOLOGIS BENIH SORGUM (Sorghum bicolor L.) - Sutariati, Gusti Ayu Kade; Khaeruni, Andi; Madiki, Abdul (Jurnal Agroteknos, 2011)
Rhizobacteria have been used for plant growth enhancement. The research was aimed on  finding  the  best  method  of  preplant  seed  treatment through  seed  invigoration plus rhizobacteria as biofertilizer to increase physiological quality of preplant sorghum   seed. The research was undertaken in Agronomy Laboratory, Agriculture Faculty, Haluoleo University, Kendari Southeast Sulawesi.    Research results showed that seed bio- matriconditioning with rhizobacteria was effective in enhancing seed quality of sorghum. The most effective treatment was the integration of seed matriconditioning using rice hull charcoal  or  ‘serbuk  bata  merah’  with  rhizobacteria  Pseudomonas  fluorescens  PG01  or Bacillus spp.CKD061. The seed treatment increased seedling growth by 120% compared to untreated seed. Based on this experiment, rhizobacteria P.fluorescens PG01 or Bacillus CKD061 integrated with   rice hull charcoal or ‘serbuk bata merah’ seed matriconditioning can be used as biological agents in improving seed quality of sorghum. Key words:   bio-matriconditioning, rhizobacteria, seed quality, sorghum